2015
DOI: 10.1038/srep07749
|View full text |Cite
|
Sign up to set email alerts
|

No DNA damage response and negligible genome-wide transcriptional changes in human embryonic stem cells exposed to terahertz radiation

Abstract: Terahertz (THz) radiation was proposed recently for use in various applications, including medical imaging and security scanners. However, there are concerns regarding the possible biological effects of non-ionising electromagnetic radiation in the THz range on cells. Human embryonic stem cells (hESCs) are extremely sensitive to environmental stimuli, and we therefore utilised this cell model to investigate the non-thermal effects of THz irradiation. We studied DNA damage and transcriptome responses in hESCs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 41 publications
5
42
0
2
Order By: Relevance
“…Furthermore, few experimental reports demonstrated THzinduced genotoxicity in human lymphocytes [23], phosphorylation of H2AX as consequence of DSBs formation in artificial human skin tissues [30], spindle disturbances in human-hamster hybrid cells [24], or changes in gene expression and activation of apoptosis and necrosis in human dermal fibroblasts and Jurkat cells [34,49]. Conversely, different studies reported no DNA damage after in vitro THz exposure evaluated by the comet assay [20,22,50], by the MN test [20,22], by analysis of H2AX phosphorylation [31] and by the expression of DNA sensing and repair genes [35].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, few experimental reports demonstrated THzinduced genotoxicity in human lymphocytes [23], phosphorylation of H2AX as consequence of DSBs formation in artificial human skin tissues [30], spindle disturbances in human-hamster hybrid cells [24], or changes in gene expression and activation of apoptosis and necrosis in human dermal fibroblasts and Jurkat cells [34,49]. Conversely, different studies reported no DNA damage after in vitro THz exposure evaluated by the comet assay [20,22,50], by the MN test [20,22], by analysis of H2AX phosphorylation [31] and by the expression of DNA sensing and repair genes [35].…”
Section: Discussionmentioning
confidence: 92%
“…Besides, an increase in the levels of several proteins involved in cell-cycle regulation and tumor suppression was reported, suggesting that DNA repair mechanisms are quickly activated [30]. Conversely, in a recent study Bogomazova et al, did not recognize the formation of H2AX phosphorylation foci or structural chromosomal aberrations in human embryonic stem cells [31].…”
Section: Introductionmentioning
confidence: 95%
“…Given that no obvious temperature rise was observed in these studies, most of the results are associated with proposed nonthermal effects of low-level THz irradiation, wherein THz radiation induced lowfrequency collective biomolecular vibrations [90]. However, the most recent evidence indicated no obvious DNA [ 2 2 _ T D $ D I F F ] damages or negligible gene changes for some ranges of THz radiation, such as 2.3 THz [93]; additionally, the observed DNA [ 2 2 _ T D $ D I F F ] damages may be effectively repaired [89]. These controversial results can be attributed to our limited understanding of the nonthermal effects of THz at the biomolecule level because of a lack of applicable modern tools [85].…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 93%
“…The genotoxic action of terahertz radiation on the frequency of induction of DNA double strand breaks in human stem cells was estimated. The ability of terahertz radiation to cause chromosomal aberrations in irradiated cells was studied [45].…”
Section: F Non-thermal Influence Of Terahertz Radiation On Escherichmentioning
confidence: 99%